Clinical picture, diagnosis and management of diabetic retinopathy for primary care physician - Praveen Vashist; Meenakshi Wadhwani (Wolters Kluwer Medknow Publications, 2015)
Diabetes is a major public health problem in our country and diabetic retinopathy is one of the important complications of diabetes. It is emerging as an important cause of visual impairment. The diagnosis and treatment facilities for diabetic retinopathy are currently limited to the tertiary level hospitals and are grossly insufficient to meet the need of population. Early detection of diabetic retinopathy and its treatment remains a major challenge for the health care providers. The current article provides information about clinical picture, screening and diagnostic criteria for diabetic retinopathy for the physicians and general practitioners working at primary level. This will be helpful in creating awareness among them about the health condition. These practitioners will be able to participate in screening of diabetic patients and their referral for diabetic retinopathy to the higher centres. Their involvement is expected to achieve prevention of visual impairment and blindness due to diabetic retinopathy.